Muscle length: A new feature to investigate neural control of lengthening contractions - Jubeau, M.; Doguet, V. (Experimental Physiology, 2020)
The central nervous system regulates skeletal muscles in all motor tasks, such as walking, jumping and running, and adopts unique strategies during lengthening muscle contractions compared with static or shortening muscle contractions (for a detailed review, see Duchateau & Enoka, 2016). This unique neural strategy has been suggested because of the reduced EMG activity or lower voluntary activation level during maximal voluntary lengthening contractions compared with either static or shortening contractions (Duchateau & Enoka, 2016).